Perhitungan Marjin Kontribusi Job Number 605169411 dengan Metode Cost-Volume-Profit - Muhammad Abani Latif (Journal of Applied Accounting and Taxation, 2016)
This research conducted that engages in mechanical assembly of printed circuit boards using robotic technology. The purpose of this research is to determine the costs contained in the production process of a project by job number 605169411, determine the amount of the contribution margin and calculate the operating income on the job. Data collection techniques used were observation. The analytical method used is descriptive analysis method. The data used is data in February until May 2016. Results of this research is the list of cost identified in the job number 605169411, the value of the contribution margin in February until May 2016, and operating income companies on the job number 605169411.